2018
DOI: 10.1128/aem.01512-18
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Iron Uptake Pathways in the Model Cyanobacterium Synechocystis sp. Strain PCC 6803

Abstract: Cyanobacteria are foundational drivers of global nutrient cycling, with high intracellular iron (Fe) requirements. Fe is found at extremely low concentrations in aquatic systems, however, and the ways in which cyanobacteria take up Fe are largely unknown, especially the initial step in Fe transport across the outer membrane. Here, we identified one TonB protein and four TonB-dependent transporters (TBDTs) of the energy-requiring Fe acquisition system and six porins of the passive diffusion Fe uptake system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 57 publications
(84 reference statements)
0
61
0
Order By: Relevance
“…Genes encoding components of siderophore synthesis are absent in this species (Hopkinson and Morel, 2009), but it is able to use siderophores produced by other organisms, such as FOB, schizokinen, aerobactin (Kranzler et al, 2011) or hydroxamate siderophores produced by the cyanobacterium Anabaena variabilis ATCC 29413 (Babykin et al, 2018;Obando et al, 2018). One TonB protein and four TBDTs are present in Synechocystis 6803, and expression of the TonB gene and of the TBDT-encoding genes was induced by iron limitation (Qiu et al, 2018). Moreover, a mutant disrupted for the TonB gene showed defective growth on low iron medium, and a quadruple mutant in which the four TBDTs were inactivated showed induction of iron uptake genes such as futA and feoB (Qiu et al, 2018).…”
Section: Synechocystis Sp Strain Pcc 6803 As a Model Cyanobacteriummentioning
confidence: 98%
See 3 more Smart Citations
“…Genes encoding components of siderophore synthesis are absent in this species (Hopkinson and Morel, 2009), but it is able to use siderophores produced by other organisms, such as FOB, schizokinen, aerobactin (Kranzler et al, 2011) or hydroxamate siderophores produced by the cyanobacterium Anabaena variabilis ATCC 29413 (Babykin et al, 2018;Obando et al, 2018). One TonB protein and four TBDTs are present in Synechocystis 6803, and expression of the TonB gene and of the TBDT-encoding genes was induced by iron limitation (Qiu et al, 2018). Moreover, a mutant disrupted for the TonB gene showed defective growth on low iron medium, and a quadruple mutant in which the four TBDTs were inactivated showed induction of iron uptake genes such as futA and feoB (Qiu et al, 2018).…”
Section: Synechocystis Sp Strain Pcc 6803 As a Model Cyanobacteriummentioning
confidence: 98%
“…Ferrous iron would then be transported into the cell by the FeoB protein and/or by divalent metal ion transporters (NRAMP or ZIP transporters for picocyanobacteria) (Hopkinson and Barbeau, 2012). Iron may be transported across the outer membrane to the periplasm by an active mechanism mediated by a TBDT, or a passive diffusion mechanism mediated by porins, which are trimeric outer membrane β-barrel proteins (Qiu et al, 2018). When it reaches the periplasm, ferric iron is bound by FutA2, generating a chemical gradient to facilitate iron influx (Kranzler et al, 2014).…”
Section: Reductive Iron Uptake and Uptake Of Inorganic Ferric Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has suggested that TBDRs of Synechocystis sp. PCC 6803 mediate the uptake of free iron, thereby not restricting iron uptake to only ferric-siderophore complexes 21 . The transport of ferrous iron across the inner membrane is mainly facilitated by Feo and divalent metal ion transporters such as MntH and ZupT 20 .…”
Section: Introductionmentioning
confidence: 99%